Non Contrast Roentgenology Diagnostic of Necrotizing Enterocolitis (NEC) in Newborns (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This is a non-specific inflammatory disease caused by infectious agents against a background of immature local defense mechanisms and hypoxia. Ischemic - this is a non-specific inflammatory disease that occurs against a background of ischemic intestinal mucosal damage. The mortality rate is 23-38%. Necrotizing enterocolitis (NEC) in newborns (necrotizing enterocolitis, necrotizing enterocolitis, ulcerative enterocolitis) necrotizing enterocolitis, necrotizing enterocolitis ulcerosa, "premature survival") is a non-specific inflammatory disease of the newborn. Inflammatory diseases of the newborn (necrotizing enterocolitis, ulcerative necrotizing enterocolitis, "premature survival") are non-specific inflammatory diseases caused by infectious agents against the background of immature local defense mechanisms. It is a non-specific inflammatory disease caused by infectious agents against a background of immature local defense mechanisms and hypoxic-ischemic enteritis.